AI-Driven Language Learning: Transforming English Pedagogy in the Digital Era - Lusiana Dewi Kusumayati; Meita Maharani; Fatmawati Fatmawati; Dimas Arya Soeadyfa Fridyatama; Faoyan Agus Furyanto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This research aims to: 1) analyze the perception of flight instructors regarding the use of artificial intelligence (AI) in English language learning; 2) To explore the experience of aviation cadets in using AI technology to improve the technical English skills; 3) To identify the benefits felt by flight cadets and instructors in the application of AI in English learning; 4) To explore the challenges faced by aviation instructors and cadets in the implementation of AI technology in English language learning, especially in the context of technical and emergency communication in the aviation world. This research was carried out at the Surabaya Civil Aviation Polytechnic from June to July 2024. The subject of this research is the cadets of Air Navigation Engineering of the Surabaya Civil Aviation Polytechnic for the 2024/2025 Academic Year, consisting of 22 cadets. The method used in this study is qualitative research. In collecting data, the authors used interviews, classroom observations, and documentation. The researcher analyzed the data using data reduction, data display, and conclusion drawing. The result of this study showed that AI played a role as a teaching assistant that helped speed up the correction process, provide training, and increase the involvement of cadets in the learning process. It is expected to provide input for the use of Artificial Intelligence (AI) in English learning, especially improving speaking skills for Air Navigation Engineering cadets of the Surabaya Aviation Polytechnic, and to arouse enthusiasm for lecturers to improve and improve the quality of the learning process